2016
DOI: 10.5152/ucd.2015.2886
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosal pseudolipomatosis: Are we aware of it?

Abstract: Objective: Colonic mucosal pseudolipomatosis is rare, and its pathogenesis is controversial. A number of mechanisms, including mechanical injury during an endoscopic procedure or chemical injury by disinfectant, seem to contribute to its pathogenesis. Results:We found pseudolipomatosis in 14 of 1370 colonoscopy cases (1.02%). Of these 14 patients, 8 were male and 6 were female. The male patients were between 24 and 66 years, with a mean of 39; the female patients were between 26 and 58 years, with a mean of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…The diagnosis of pseudolipomatosis could be challenging and misleading especially when both endoscopists and pathologists are not aware of it. 2,4,11 The clinical presentation is often asymptomatic or related to associated diseases (diarrhea, constipation and so on). The characteristic endoscopic findings in colic pseudolipomatosis are white or yellow, flat to slightly elevated plaques, phenomenon described as the “snow white sign.” 1,6 However, these characteristic endoscopic patterns may be absent like in our current patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of pseudolipomatosis could be challenging and misleading especially when both endoscopists and pathologists are not aware of it. 2,4,11 The clinical presentation is often asymptomatic or related to associated diseases (diarrhea, constipation and so on). The characteristic endoscopic findings in colic pseudolipomatosis are white or yellow, flat to slightly elevated plaques, phenomenon described as the “snow white sign.” 1,6 However, these characteristic endoscopic patterns may be absent like in our current patient.…”
Section: Discussionmentioning
confidence: 99%
“…These spaces are embedded in the lamina propria and intermingled with inflammatory cells without destruction of glandular structures, and usually the inflammatory cells seem to line the empty spaces suggesting vascular structure or adipocytes. 1,2,4,7 Also, these spaces could have discrete eosinophilic amorphous content. 7 We have found focally empty spaces with these eosinophilic content in our current case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al identified 12 cases with colonic pseudolipomatosis among 1,276 colonoscopies (0.94%) ( 2 ). The reported frequency ranges from 0.02% to 1.7% among all colonoscopies performed ( 2 , 3 , 6 - 9 ). Several mechanisms, such as chemical injury by a disinfectant, particularly hydrogen peroxide, and mechanical injury during an endoscopic procedure, have been hypothesized for the pathogenesis of colonic pseudolipomatosis ( 2 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medical literature does not suggest a predilection for a specific age or sex in the prevalence of reported cases of colonic pseudolipomatosis. 5…”
Section: What Is Your Diagnosis?mentioning
confidence: 99%